SELF-EFFICACY AS A PREDICTOR OF STUDENTS’ QUR’ANIC MEMORIZATION ACHIEVEMENT THROUGH THE SIMA’AN AND TALAQQI METHODS - Nili Ariyani; Ajahari Ajahari; Abdullah Abdullah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to examine the role of self-efficacy as a predictor of students’ Qur’anic memorization success through the implementation of the Sima’an and Talaqqi methods at Hidayatul Insan Islamic Boarding School, Palangka Raya. Employing a mixed-methods approach with a convergent parallel design, data were collected from 35 active tahfidz students through observations, semi-structured interviews, documentation, and a Likert-scale questionnaire consisting of 21 items. Quantitative data were analyzed using correlation and regression tests, while qualitative data were examined through thematic analysis to strengthen the interpretation of statistical findings.The results indicated that self-efficacy had a strong and significant relationship with Qur’anic memorization success (r = 0.731; p < 0.001), as did the implementation of the Sima’an–Talaqqi method (r = 0.756; p < 0.001). Regression analysis confirmed that both variables significantly predict memorization achievement, with the Sima’an–Talaqqi method contributing the strongest effect. Qualitative findings further revealed that students with high self-efficacy demonstrated greater confidence, persistence, and consistency in conducting murāja‘ah, while structured repetition and direct supervision through Sima’an and Talaqqi enhanced memorization accuracy and stability.These findings implied that successful tahfidz learning required the integration of psychological readiness and systematic instructional methods. Islamic boarding schools were therefore encouraged to strengthen students’ self-efficacy alongside the consistent implementation of Sima’an and Talaqqi to optimize Qur’anic memorization outcomes.